Variable and bidirectional steam flow apparatus and method - GIDDINGS; JOHN R (1998)
A valve apparatus for a turbomachine comprises a manifold casing, a valve lift assembly, and a plurality of valve assemblies. The manifold casing defines a valve inlet chamber and has a top wall and a bottom wall with a plurality of vertically disposed openings through the top wall and a plurality of openings to vertically disposed passages in the bottom wall. The passages each extend away from the bottom wall to a passage exit. The valve lift assembly comprises a plurality of lift bars and a plurality of lift pins. The lift pins extend vertically through the vertically disposed openings at the top wall of the manifold casing. A plurality of valve assemblies equal in number to that of vertically disposed passages in the bottom wall each comprise a valve configured to fit scalingly against the corresponding vertically disposed opening and a valve stem with one end connected to a corresponding valve and an opposite end connected to a valve stop shoulder to place each of the valve assemblies in movable association with at least one of said lift bars.